The activity profile of elite male amateur boxing after the 2013 rule changes - Davis, P.; Connorton, A. J.; Driver, S.; Anderson, S.; Waldock, R. (The Journal of Strength and Conditioning Research, 2018)
An activity profile of competitive elite amateur boxing after the rule changes in 2013 was created from video footage to allow identification of the technical and tactical demands as well as differences between winners and losers. The study analyzed 50 World Championship bouts involving 60 male boxers (mean ± SD) of age: 23.5 ± 2.8 years, height: 176.2 ± 12.2 cm, and body mass: 71.7 ± 16.2 kg. The results establish that boxing at this level requires the ability to maintain an activity rate of ~1.55 actions per second, consisting of ~21 punches, ~3.6 defensive movements, and ~56 vertical hip movements all per-minute. Winners had a higher amount of straight punches and straight punches lead hand in round 1 (both p < 0.043) along with total punches landed in round 3 (p = 0.030). They also had a lower ratio of punches thrown to punches landed in round 3 and air punches as a percentage of missed in round 2 and 3 (both p < 0.015). The results suggest that a winning strategy must include the straight punch technique from both lead and rear hands and the ability to increase punching accuracy over subsequent rounds. Tactically, boxing has become long range with straight punches, increased defense and movement around the ring, in contrast to short-range hooks as seen pre-2013. These changes should be considered when creating new training strategies.